The Future of Indigenous Health Policy in Manitoba: Moving Beyond Soft Reconciliation in Health - Gabel, Chelsea; Powell, Alicia (Western University, 2023)
This article examines the changing nature of Indigenous healthcare and policy in Manitoba focusing on two critical healthcare gaps in the province: the health transfer policy, a policy that continues to be counterproductive to Indigenous health and well-being; and the intended closure of Grandview’s EMS station and its failure to consider First Nations and Métis perspectives and access to care. Drawing on over a decade of community-engaged research in the province, our research argues for the need to move beyond soft reconciliation efforts in Indigenous health to reinterpreting Canada’s colonial history by recognizing Indigenous peoples’ hard rights to healthcare. Reconciliation should bring about changes to bureaucratic structures and challenge non-Indigenous peoples’ values. Health system changes in Indigenous communities, without consultation, will continue to negatively impact community life and wellbeing. This article is intended to contribute to a broader discussion about the future of Indigenous healthcare, policy and reconciliation efforts in Manitoba.